Effect of rapid surface cooling on Campylobacter numbers on poultry carcasses. (December 2016) - Burfoot, Dean; Hall, Jeremy; Nicholson, Keith; Holmes, Kirsty; Hanson, Cedric; Handley, Simon; Mulvey, Elizabeth
Abstract: These studies examined the effect of rapid surface cooling on the numbers of Campylobacter on chicken carcasses. In two trials, chicken skins were immersed in liquid nitrogen. Campylobacter numbers were reduced by 1 log10  cfu/g by immersion for 20s. Immersion would not be practical for whole carcasses in commercial slaughterhouses. Twenty two trials investigated the effects of spraying liquid nitrogen towards whole carcasses either in a chamber or in a tunnel. The final four trials, with carcasses passing through a spray tunnel for 40s, caused average reductions in the numbers of Campylobacter of between 0.9 and 1.5 log10  cfu/g when tested the day after treatment and between 0.9 and 1.3 log10  cfu/g when tested a further six days later. The temperature of the flesh remained above −2 °C thereby showing that the flesh was not frozen by the process which offers a viable approach to reducing Campylobacter on chicken carcasses. Highlights: Rapid surface cooling of Campylobacter on chicken carcasses was examined. Immersion of skin in liquid nitrogen for 20 s caused a 1 log10  cfu/g reduction. Spraying with liquid nitrogen for 40 s caused a 0.9 to 1.5 log10  cfu/g reduction. The flesh was not frozen by the treatment.